On the Equivalence between Integer-and Fractional Order-Models of Continuous-Time and Discrete-Time ARMA Systems - Ortigueira, Manuel Duarte (2022)
Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.